Effectiveness of animation-based learning in enhancing elementary students' cognitive achievement in science - Umdatussalik; Wibowo, Eko; Juhji (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2025)
This study aims to analyze the effectiveness of using animation media in science learning to improve students' cognitive learning outcomes on the material of the solar system arrangement. This study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The research sample consisted of 58 grade VI students, who were divided into experimental groups (n = 29) who received learning assisted by animated media and control groups (n = 29) who received conventional learning. The analysis showed that there was a significant difference in cognitive learning outcomes between the two groups, with a significance value of 0.000 <0.05, so the alternative hypothesis (Ha) was accepted. The average pretest score of the experimental group was 49.90 and increased to 83.48 on the post-test after the treatment. The average pretest score of the control group was 63.90, with an increase to 70.76 in the post-test. The results of this study concluded that the use of animated media in science learning in elementary schools significantly contributed to the improvement of students' cognitive learning outcomes on the concept of the solar system arrangement. Based on these findings, it is recommended that educators make more use of animated media as a tool in learning science, especially on abstract concepts such as the composition of the solar system. Keywords: animation, learning outcomes, learning media, solar system